ALBI grade for outcome prediction in patients affected by hepatocellular carcinoma treated with transarterial radioembolization - Gelardi, Fabrizia; Rodari, Marcello; Pini, Cristiano; Zanca, Roberta; Artesani, Alessia; Tosi, Giovanni; Chiti, Arturo; Sollini, Martina (Frontiers in Nuclear Medicine, 2022)
Introduction and aim: Diagnosis of hepatocellular carcinoma (HCC) often occurs when disease is unresectable and therapeutic options are limited. The extent of disease and liver function according to Child-Pugh (C-P) classification are the main prognostic factors guiding clinicians in management of HCC. The ALBI grade is emerging to assess liver function on account of its objectivity and reproducibility. Our aim was to investigate the value of the ALBI grade in predicting the outcome in patients treated with transarterial radioembolization (TARE). Methods: We retrospectively enrolled patients with advanced and unresectable HCC treated with TARE in our institution. All patients underwent a preliminary dosimetric study before Yttrium-90 resin microspheres TARE. BCLC, C-P and ALBI score were established at the time of TARE. Overall survival (OS), Progression Free Survival (PFS) and survival after TARE were assessed with Kaplan-Meier method. Survival analyses were stratified according to ALBI score, C-P, and BCLC classification. Univariate and multivariate Cox proportional regression models determined the association between prognostic factors and clinical outcome. Results: Seventy-two patients were included in the study, showing an OS of 51 months. The ALBI grade identified groups of patients with different prognosis both in the whole cohort and within the C-P classes, especially between ALBI 1 and ALBI 2. This result is confirmed also within BCLC classes. In treatment naïve patients, the ALBI grade was not able to predict outcome, whereas the presence and degree of portal vein thrombosis significantly affected prognosis. Conclusions: The ALBI grade provided a more accurate prognostic stratification than the C-P classification in patients with intermediate and advanced HCC treated with TARE. However, the outcome of HCC is affected not only by liver function, but also by disease-related characteristics such as disease burden and degree of PVT. Including the ALBI grade in clinical guidelines may improve the management of patients affected by HCC.